Reverse darning technique: an effective and innovative method of inguinal hernia repair - George, Robinson; Radhakrishna, Veerabhadra; Mathew, Mebin; Rahman, Ashna; Thenamangalath, Aswini (International Surgery Journal, 2019)
Background: Laparoscopic mesh repair is the standard of care for inguinal hernias. But, our center being in a rural setup catering mainly poor patients who are daily wagers and laborers, open repairs are commonly done. Lichtenstein’s tension-free mesh repair is the standard technique used worldwide. This study was performed to compare the effectiveness of Reverse darning repair over traditional mesh repair in a rural setup and to reciprocate the changes generally. The outcomes such as postoperative pain, seroma formation, postoperative analgesic use, and the recurrence rate were compared. Methods: Retrospective analysis of patients who had undergone mesh repair and reverse darning procedure between January 2013 and December 2017 was performed in a rural tertiary center. Results: The reverse darning group was found to have significantly lesser mean duration of surgery (15.7±1.7 min. vs. 31.2±2.5 min.; t=37.4, p<0.005), analgesic use (4.4±1.2 doses vs. 7.4±1.3 doses; t=12.2, p<0.005), hospital stay (39.4±8.2 hours vs. 58.1±9.5 hours; t=10.7, p<0.005), and the cost of treatment (Rs. 5188±286 vs. Rs. 7154±1290; t=11.6, p<0.005) compared to the Lichtenstein group. The Reverse daring group was also better than Lichtenstein repair in terms of seroma formation (1 vs. 7; chi-square value=7.9; p=0.005), hematoma (0 vs. 6; chi-square value=9.4, p=0.002), and secondary hydrocele (1 vs. 5; chi-square value=4.9, p=0.03). Conclusions: Reverse darning repair was found to be much better than traditional mesh repair due to its simplicity, lesser duration of surgery, hospital stay, cost of treatment, and postoperative complications.